ANALYSIS OF FOREIGN STUDIES ON THE DEVELOPMENT OF RESEARCH COMPETENCIES IN STUDENTS DURING THE ACADEMIC EDUCATION PROCESS - Abdurazakova Zebiniso Akmalxon kizi (Bright Mind Publishing, 2025)
This article aims to develop research competence based on an effective pedagogical approach that is appropriate for the developmental needs and cognitive processes of students. It provides information on what competencies a learner should have in the digital and big information age, as well as valuable insights from several educational theories about the dynamics of learning and the development of research skills.
Keywords: Axiological, socio-legal, substantive, methodological and technological, communicative, analytical management, project research, professional and pedagogical competencies.